PERBANDINGAN KERAGAAN TANAMAN KELAPA SAWIT (Elaeis guineensis Jacq.) PADA SISTEM PEREMAJAAN KONVENSIONAL DAN UNDERPLANTING - Ayu Nurjanah; Aries Sukariawan; Dina Arfianti Saragih (Institut Teknologi Sawit Indonesia, 2021)
In terms of felling the old palms, there are two techniques for oil palm replanting: conventional and underplanting. The conventional method involves felling all of the old palms at once. Under the underplanting technique, on the other hand, the old palms are felled in stages, and the new palms are planted among the remaining old palms. The purpose of this study was to compare the performance of immature oil palms when replanting old palms using conventional and underplanting techniques. The research was conducted in Kebun Rambutan, PT Perkebunan Nusantara III. In comparison to the conventional technique, immature oil palms underplanting required more insertion plants, displayed etiolation symptoms, and had a lower average bunch weight. When using underplanting techniques for oil palm replanting, it is necessary to be disciplined in the application of Best Agronomic Practices in all stages of plant maintenance.